Interactive Animation of Photosynthesis Process as an Educational Means for Elementary School Students - Ramadhani; Devi Mulia Sari; Hijrina (Jurnal Inotera, 2023)
Natural science lessons have been taught to elementary school students. In natural science lessons, there are various kinds of materials, one of which is the photosynthesis system. There are many misconceptions in conveying material using the lecture method and printed book media. Based on these problems, the role of interactive multimedia is expected to help the teaching and learning process of agriculture become easier to understand by presenting it in the form of visuals, sound and moving images. The photosynthesis animation application was designed using Adobe Illustrator to create images, Adobe After Effects and Unity to create animations and visual effects. Based on the average evaluation results on this application, elementary school students more easily understand photosynthesis material by more than 85%.